The mediating role of social connectedness and negative cognitive emotion regulation in the association between problematic Internet use and depression among adolescents - Xu, Jiaqi; Chen, Xia-Can; Chen, Lihua; Luo, Dan; Bao, Wenxin; Yang, Xia; Ran, Junzhe; Xu, Jiajun (Frontiers in Public Health, 2024)
Introduction While the relationship between adolescent problematic Internet use (PIU) and depression has been extensively researched, few studies have investigated the role and mechanisms of social connectedness (SC) in this context. This study aimed to investigate the mediating effect of social connectedness (SC) and cognitive emotion regulation (CER) in the relationship between PIU and depression. Methods We conducted a cross-sectional study involving 9,407 adolescents aged 12–18 years in China from September 2022 to March 2023. We employed Young’s 20-item Internet Addiction Test (IAT-20), the Social Connectedness Scale-Revised (SCS-R), the Cognitive Emotion Regulation Scale (CER), and the DSM-5 Level-2 Depression Scale to assess mental health outcomes. Logistic regression analysis was also performed to examine the independent association between the measured variables and depression. Mediation analysis was then conducted to evaluate the mediating roles of social connectedness and cognitive emotion regulation in the relationship between PIU and depression. Results We found that the prevalence of PIU was 21.8%. Offline SC (indirect effect: 0.112, 95% CI: 0.104–0.121) and negative CER (indirect effect: 00.140, 95% CI: 0.129–0.152) mainly played a parallel mediating role in the relationship between PIU and depression, along with online SC (on_SC) (indirect effect: 0.007, 95% CI: 0.005–0.010). Discussion These findings provide valuable insights into how PIU is associated with depression and highlight the importance of fostering real-life interpersonal interactions. However, the generalizability of this study’s findings to other populations may be limited due to cultural factors.